Neuroendocrine carcinoma of the extrahepatic bile duct: A case report - Oshiro, Yukio (World J Gastroenterol, 2016)
Neuroendocrine carcinoma (NEC) originating from the gastrointestinal hepatobiliary-pancreas is a rare, invasive, and progressive disease, for which the prognosis is extremely poor. The patient was a 72-year-old man referred with complaints of jaundice. He was diagnosed with middle extrahepatic cholangiocarcinoma (cT4N1M0, cStage IV). He underwent a right hepatectomy combined with extrahepatic bile duct and portal vein resection after percutaneous transhepatic portal vein embolization. Microscopic examination showed a large-cell neuroendocrine carcinoma according to the WHO criteria for the clinicopathologic classification of gastroenteropancreatic neuroendocrine tumors. Currently, the patient is receiving combination chemotherapy with cisplatin and etoposide for postoperative multiple liver metastases. Although NEC is difficult to diagnose preoperatively, it should be considered an uncommon alternative diagnosis.